Meta-analysis of the prevalence of physical inactivity among Brazilian adolescents Meta-análise de prevalência de inatividade física entre adolescentes brasileiros - Laura Augusta Barufaldi; Gabriela de Azevedo Abreu; Evandro Silva Freire Coutinho; Katia Vergetti Bloch (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
A systematic review and meta-analysis were carried out to investigate the prevalence of physical inactivity among adolescents in Brazil. We identified articles that had been published up to August 2010 and the search was conducted using six electronic databases. We did not enforce any search limitations. Forest plot-type graphs were generated using the prevalence of physical inactivity stratified by region and sex. Meta-regression models were fitted to identify possible sources of heterogeneity in the prevalence estimates. Of the 1,496 articles initially identified, 37 were deemed appropriate for the systematic review. Prevalence rates ranged from 2% to 80% for male and from 14% to 91% for female subgroups. The lowest prevalence rates of physical inactivity were found to be for the Southern region, whereas the highest rates were observed in the North-Northeast. The methods employed to evaluate physical inactivity in Brazilian adolescents also differed among the studies. This variation demonstrates the need for standardised and validated methods of measuring physical activity in epidemiological investigation. Foram realizadas revisão sistemática e meta-análise para investigar a prevalência de inatividade física entre adolescentes no Brasil. Identificou-se artigos publicados até agosto de 2010. A busca foi realizada em 6 bases de dados eletrônicas, não tendo sido utilizados quaisquer limites. Gráficos do tipo forest-plots foram gerados usando-se a prevalência de inatividade física estratificada por região e sexo. Modelos de metarregressão foram ajustados para identificar as possíveis fontes de heterogeneidade nas estimativas. Dos 1.496 artigos identificados inicialmente, 37 foram considerados adequados. As taxas de prevalência variaram de 2% a 80% para o gênero masculino e de 14% para 91% para o feminino. As menores taxas de prevalência foram encontradas na Região Sul, e as maiores nas regiões Norte e Nordeste. Os métodos utilizados para avaliar a inatividade física em adolescentes brasileiros também diferiram entre os estudos. Essa variação demonstra a necessidade de métodos padronizados e validados para medir a atividade física na pesquisa epidemiológica.